Study guides

Q: -2x plus 3y equals 9

Write your answer...

Submit

Related questions

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

(-1,-2)

x = 8, y = -1

The ordered pair is (-1, -2).

6x+3y = -9 3y = -6x-9 y = -2x-3 Therefore the perpendicular slope is 1/2

It is -9

x + y = -2 2x + 3y = -9 You solve this by elimination - multiply both sides of first equation by 3, then subtract, solve for x, then substitute in any of the equations to solve for y 3x + 3y = -6 2x + 3y = -9 subtracting, x = 3 substituting into 1st equation, y = -2-3 = -5

-4x + 3y = 9

The answer to 1 over 2x plus 13 equals 9 is x equals -8.

3y = 4x + 9 -4x + 3y = 9 is the standard form

2x - 3y = 5 => 3y = 2x - 5 has a gradient of 2/3 9y + bx = 4 => 9y = -bx + 4 has a gradient of -b/9 The two gradiends must be the same if the two lines are parallel: 2/3 = -b/9 so that b = -6

2y + 3 = 3y + 9 2y - 3y = 9 - 3 or -y = 6 so y = -6

2x = -x +9

To put the equation 3y - 9 = 2x in y-intercept form (y = mx + b): 3y - 9 = 2x 3y = 2x + 9 (add 9 to both sides of the equation) y = 2/3 x + 3 (divide all terms by 3) The y-intercept is the b term in the equation, which in this example is 3.

y= -9

Put in function, Y = mX + C, form. 6X + 3Y = - 9 3Y = - 6X - 9 Y = - 2X - 3 -------------------- m(slope) = - 2 ----------------------

y = (4x+9)/(2x+3)2xy+3y = 4x+93y-9 = 4x-2xy3y-9 = x(2-2y)x = (3y-9)/(2-2y)So, inverse function is 3x minus 9 divided by 2 minus 27.

4x + 3y=9 x=0 y=3

y=5x+2 if y equals -4

6x + 3y = -9 So 3y = -6x - 9 or y = -2x - 3 So the slope of the given line is -2 Therefore, the slope a any parallel line is also -2.

5x + x - 6x + 2x = 2x

x = 7

If 5 x equals 9 plus 2x then x equals?

6 + 2x = 5x + 9 , 6 - 9 = 5x - 2x , -3 = 3x , x = -1

if 2x+3=9 then 2x=6 so x=3